2020
DOI: 10.1186/s13048-020-00690-z
|View full text |Cite
|
Sign up to set email alerts
|

Follicular phase length has no influence on frozen-thawed embryo transfers in natural cycles

Abstract: Background: Whether menstrual variability in women with regular and ovulatory cycle could affect embryo implantation remains controversial, with conflicting evidences presented in the literature. Thus, in this study, we evaluated the impact of prolonged follicular phase length (FPL) on the clinical pregnancy rate (CPR) after frozenthawed embryo transfer (FET) in true natural cycles (NC). Methods: This retrospective cohort study utilized data from a large university-affiliated reproductive medicine center. Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Our results are consistent with recent studies that evaluated the association of FPL and pregnancy outcome in the context of treatment with assisted reproductive technology ( 18 , 19 ) and natural cycle frozen-thawed embryo transfer ( 11 , 20 ). All of these studies report no association between FPL and pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with recent studies that evaluated the association of FPL and pregnancy outcome in the context of treatment with assisted reproductive technology ( 18 , 19 ) and natural cycle frozen-thawed embryo transfer ( 11 , 20 ). All of these studies report no association between FPL and pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…There is no consensus in the current literature as to a specific cut-off to define short FPL. Consistent with prior studies of natural and stimulated cycles ( 11 , 12 , 13 , 14 , 15 ), this study revealed variation in length of the follicular phase ranging from 7 to 24 days. Recently published studies examined cycle phase lengths in women using mobile phone applications that track the menstrual cycle ( 12 , 14 , 15 , 16 , 17 ).…”
Section: Discussionsupporting
confidence: 90%